2017
DOI: 10.1016/j.crad.2016.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced MDCT in patients with pancreatic neuroendocrine tumours: correlation with histological findings and diagnostic performance in differentiation between tumour grades

Abstract: AIM To identify the multidetector computed tomography (MDCT) features of pancreatic neuroendocrine tumours (pNETs), which correlate with tumour histology and enable preoperative grading. MATERIALS AND METHODS Thirty-nine patients with histologically confirmed pNET who underwent preoperative contrast-enhanced MDCT were included in this study. Nineteen tumours were classified as Grade 1 (G1) and 20 as Grade 2 (G2). Histopathology slides were reviewed to assess the intratumoural microvascular density (MVD) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…The development of the NET test, a multianalyte liquid biopsy that measures NET gene expression, has shown promising results in diagnosis and predictive therapeutic assessment, and might also help individualize NET G−3. Some works have shown that radiology, such as contract-enhanced multidetector computed tomography, can help distinguish pathological grades, in particular G−1 from G−2 pancreatic NET [89]. Future radiological studies might allow to help distinguish NET G−3 from NEC or NET G−3.…”
Section: Further Areas Of Researchmentioning
confidence: 99%
“…The development of the NET test, a multianalyte liquid biopsy that measures NET gene expression, has shown promising results in diagnosis and predictive therapeutic assessment, and might also help individualize NET G−3. Some works have shown that radiology, such as contract-enhanced multidetector computed tomography, can help distinguish pathological grades, in particular G−1 from G−2 pancreatic NET [89]. Future radiological studies might allow to help distinguish NET G−3 from NEC or NET G−3.…”
Section: Further Areas Of Researchmentioning
confidence: 99%
“…Due to the excellent spatial and time resolution of multi-detector CT (MDCT), it is possible to obtain information on tumor characteristics related to pathologic grades. Recent studies have reported that specific CT features can help to differentiate poorlydifferentiated gastric NENs from well-differentiated NENs, and are useful in the pathological classification of pancreatic NENs (11)(12)(13)(14). However, to the best of our knowledge, no published studies have yet focused on comparing the CT features of the LMs of well-and poorlydifferentiated GEP-NENs.…”
Section: Introductionmentioning
confidence: 99%
“…While DWI alone is less sensitive than a gadoxetic acid-enhanced MRI in detecting liver metastases, it increases the sensitivity of detection for liver metastases to 90.6-95.5%, when combined with DCE-MRI [35]. [36]. Third generation DECT, with an assessment of iodine uptake, improves the differentiation of hepatic NET metastasis and hepatocellular carcinoma (HCC) in noncirrhotic livers, as shown in a study by Kaltenbach et al that examined 46 patients with either hepatic NEN metastasis or HCC, all of whom had undergone liver DECT in a retrospective study [37].…”
Section: Discussionmentioning
confidence: 99%